Forgot to Exercise? Exercise Derived Circulating Myokines in Alzheimer's Disease: A Perspective - Gupta, Rajesh; Khan, Rizwan; Cortes, Constanza J. (Frontiers in Neurology, 2021)
Regular exercise plays an essential role in maintaining healthy neurocognitive function and central nervous system (CNS) immuno-metabolism in the aging CNS. Physical activity decreases the risk of developing Alzheimer’s Disease (AD), is associated with better AD prognosis, and positively affects cognitive function in AD patients. Skeletal muscle is an important secretory organ, communicating proteotoxic and metabolic stress to distant tissues, including the CNS, through the secretion of bioactive molecules collectively known as myokines. Skeletal muscle undergoes significant physical and metabolic remodeling during exercise, including alterations in myokine expression profiles. This suggests that changes in myokine and myometabolite secretion may underlie the well-documented benefits of exercise in AD. However, to date, very few studies have focused on specific alterations in skeletal muscle-originating secreted factors and their potential neuroprotective effects in AD. In this review, we discuss exercise therapy for AD prevention and intervention, and propose the use of circulating myokines as novel therapeutic tools for modifying AD progression.